PENERAPAN MODEL PEMBELAJARAN TEAM GAME TOURNAMENT UNTUK MENINGATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI 184 HUTATONGA - Riska Ramadani; Parulian Siregar; Lia Agustina Damanik (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to determine the improvement in student learning outcomes through the application of the Team Game Tournament learning model in energy learning and its changes in class IV students at SD Negeri 184 Hutatonga. This research is classroom action research involving 16 students, 7 men and 9 women. Which takes place in two cycles. This data was collected using observation sheets and test questions. The results of this research show that student learning activity in cycle I was 61.66% and increased in cycle II, namely 95%. And student learning outcomes in cycle I, namely 68, 37 %, increased in cycle II, namely 82.5%. Based on data analysis, it can be concluded that the application of the Team Game Tournament learning model can improve the learning outcomes of class IV students at SD Negeri 184 Hutatonga.